Managing sustainable development of government link companies (GLCs) in Malaysia through emotional intelligence and organisational politics - Wan Hanafi W.N. (Inderscience Publishers, 2023)
Surveys; Sustainable development; Leader-member exchange theories; Malaysia; Organisational; Partial least square (PLS); Research frameworks; Stratified random sampling; Structural equation modeling; Emotional intelligence